Recombination fraction and genetic linkage among key disease resistance genes (Co-4 2 /Phg-2 and Co5/“P.ult”) in common bean - Okii, Dennis; Badji, Arfang; Odong, Thomas L.; Talwana, Herbert; Tukamuhabwe, Phineas; Male, Allan; Mukankusi, Clare Mugisha; Gepts, Paul L. (Academic Journals, 2019)
Anthracnose (Colletotrichum lindemuthianum), Angular leaf spot (Pseudocercospora griseola) and Pythium root rot are important pathogens affecting common bean production in the tropics. A promising strategy to manage these diseases consists of combining several resistance (R) genes into one cultivar. The aim of the study was to determine genetic linkage between gene pairs, Co-42/Phg-2, on bean-chromosome Pv08 and Co-5/"P.ult" on-chromosome Pv07, to increase the efficiency of dual selection of resistance genes for major bean diseases, with molecular markers. The level of recombination was determined by tracking molecular markers for both BC3F6 and F2 generations. Recombination fraction r, among gene pairs, the likelihood of linkage, L(r), and logarithm of odds (LOD) scores were computed using the statistical relationship of likelihood which assumes a binomial distribution. The SCAR marker pair SAB3/PYAA19 for the gene pair Co-5/"P.ult" exhibited moderate linkage (r = 32 cM with a high LOD score of 9.2) for BC3F6 population, but relatively stronger linkage for the F2 population (r = 21 cM with a high LOD score of 18.7). However, the linkage among SCAR marker pair SH18/SN02, for the gene pair Co-42/Phg-2 was incomplete for BC3F6 population (r = 47 cM with a low LOD score of 0.16) as well as F2 population (r = 44 cM with a low LOD score of 0.7). Generally, the weak or incomplete genetic linkage between marker pairs studied showed that all the four genes mentioned earlier have to be tagged with a corresponding linked marker during selection. The approaches used in this study will contribute to two loci linkage mapping techniques in segregating plant populations.